Assumptions and opportunities for development of investigational competency at students [Articol] - Șevciuc, Maia (Editografica, 2018)
The scientific-investigative activity of students is an important factor in self-regulation of knowledge and affirmation, as well as for the quality of specialist training and their integration into the labour market. Therefore, at the moment the scientific investigative competency and experimental constructive of students becomes of outmost importance in their process of professional development. For this purpose we have set the goal of pointing out the necessity, the context, as well as the opportunities for the development of the investigative competency amongst students. Another goal was to elaborate on the criteria and indicators of assessing the level of investigative competency building among them. We consider that the theoretical aspects reflected in the article represent an opening for practical and applicative contexts in the development of investigative competency of students.
Keywords: investigational competency of students; level of training for research activity